The Usborne Encyclopedia Of The Ancient World - Jane Bingham, Fiona Chandler, Jane Chisholm, Gill Harvey, Lisa Miles, Struan Reid & Sam Taplin
Provides information on the cultures and histories of Mesopotamia, Egypt, Greece, and the Roman Empire.